2021
DOI: 10.3389/frsen.2021.778691
|View full text |Cite
|
Sign up to set email alerts
|

Observing Sucrose Accumulation With Sentinel-1 Backscatter

Abstract: In this study the impact of sucrose accumulation in Sentinel-1 backscatter observations is presented and compared to Planet optical observations. Sugarcane yield data from a sugarcane plantation in Xinavane, Mozambique are used for this study. The database contains sugarcane yield of 387 fields over two seasons (2018-2019 and 2019-2020). The relation between sugarcane yield and Sentinel-1 VV and VH backscatter observation is analyzed by using the Normalized Difference Vegetation Index (NDVI) data as derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…High-performance seasons exhibit lower Biomass Proxy values pre-harvest compared to low-performance seasons. This phenomenon was first discovered in Mozambique by den Besten et al in [27] and further investigated in [59]. The authors found that the CR responds to the development of sucrose accumulation, which changes the internal distribution of sucrose and vegetation water in the stalk.…”
Section: Example 4: Biomass Proxy and Ndvi Time Series And Their Comp...mentioning
confidence: 88%
See 1 more Smart Citation
“…High-performance seasons exhibit lower Biomass Proxy values pre-harvest compared to low-performance seasons. This phenomenon was first discovered in Mozambique by den Besten et al in [27] and further investigated in [59]. The authors found that the CR responds to the development of sucrose accumulation, which changes the internal distribution of sucrose and vegetation water in the stalk.…”
Section: Example 4: Biomass Proxy and Ndvi Time Series And Their Comp...mentioning
confidence: 88%
“…Additionally, it has been shown that optical indices provide important insights in the spatial distribution of crop biomass [25,26]. Tracking the growth of crop biomass is essential as it is directly linked to crop yield [27,28] and can be used to refine agricultural practices like variable rate applications of fertilizers, pesticides, or irrigation [29].…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane ( Saccharum officinarum L.) is a very valuable crop used for the manufacture of sugar and bioethanol [ 1 ]. The amount and quality of the soluble sugar, mainly sucrose, directly affect the sugar yield in sugarcane [ 2 ]. Sugarcane is a major source of sucrose, which is used as the principal source of sugar in human consumption, animal feed, and biofuel generation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%